1988
DOI: 10.1126/science.3277284
|View full text |Cite
|
Sign up to set email alerts
|

Site-Directed Mutagenesis of Two Trans-Regulatory Genes ( tat -III, trs ) of HIV-1

Abstract: Point mutations were introduced into the overlapping trans-regulatory genes (tat-III and trs) of human immunodeficiency virus type 1 (HIV-1), and the mutants were evaluated for virus expression. The results showed that tat-III has a positive transacting role and is required for transcriptional activation. A chain terminating mutation early in the trs gene resulted in an increase in transcription of viral messenger RNA as measured by nuclear transcription experiments, but only one major species of viral messeng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
113
0
1

Year Published

1988
1988
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(117 citation statements)
references
References 28 publications
(25 reference statements)
3
113
0
1
Order By: Relevance
“…É ric A. Cohen (IRCM, Canada) provided the HxBRUDp6 in which a stop codon was introduced following the p6 ORF (Gottlinger et al 1991). David Ott (NIH/NCI, Frederick, MD) provided the pNL4-XX and pNL4-X proviral constructs as described (Poon et al 2002); and the NIH AIDS Reference and Reagent Program provided the pMRev(À) contruct (Sadaie et al 1988). Anne Gatignol (McGill University) provided the pMAL and pADA Mtropic proviral constructs.…”
Section: Cell Lines and Transfectionsmentioning
confidence: 99%
“…É ric A. Cohen (IRCM, Canada) provided the HxBRUDp6 in which a stop codon was introduced following the p6 ORF (Gottlinger et al 1991). David Ott (NIH/NCI, Frederick, MD) provided the pNL4-XX and pNL4-X proviral constructs as described (Poon et al 2002); and the NIH AIDS Reference and Reagent Program provided the pMRev(À) contruct (Sadaie et al 1988). Anne Gatignol (McGill University) provided the pMAL and pADA Mtropic proviral constructs.…”
Section: Cell Lines and Transfectionsmentioning
confidence: 99%
“…Several mechanisms have been proposed to explain its action, including enhancement of HIV-1 LTR-directed transcription rate (Jakobovits et al 1988;Jeang et al 1988; Rice and Mathews 1988;Laspia et al 1989), increase in mRNA stability (Muesing et al 1987), anti-termination of transcription within the R region of the LTR (Kao et al 1987;Selby et al 1989;Toohey and Jones 1989), and enhancement of translation of HIV-1 mRNAs (Rosen et al 1986a;Feinberg et al 1986;Braddock et al 1989). Bimodal mechanisms involving transcriptional and post-transcriptional events have also been suggested (Cullen 1986;Wright et al 1986;Sadaie et al 1988).…”
mentioning
confidence: 99%
“…Tat produces a large stimulation of HIV-1-promoted RNA levels (CuUen 1986;Peterlin et al 1986;Wright et al 1986;Hauber et al 1987;Muesing et al 1987;Rice and Mathews 1988a) so the predominant mode of regulation appears to be transcriptional (Hauber et al 1987;Kao et al 1987;Jakobovits et al 1988;Jeang et al 1988;Rice and Mathews 1988a;Sadaie et al 1988;Laspia et al 1989), but evidence for posttranscriptional regulation also exists (Cullen 1986;Fein-Cold Spring Harbor Laboratory Press on April 4, 2019 -Published by genesdev.cshlp.org Downloaded from berg et al 1986;Rosen et al 1986;Wright et al 1986;Braddock et al 1989Braddock et al , 1990). In a model system consisting of replicating plasmids in COS cells, Kao et al (1987) found that Tat does not increase the initiation of transcription but act to stimulate transcriptional elongation.…”
mentioning
confidence: 99%